2011
DOI: 10.1155/2012/831524
|View full text |Cite
|
Sign up to set email alerts
|

Ti3+ in the Surface of Titanium Dioxide: Generation, Properties and Photocatalytic Application

Abstract: Titanium dioxide (TiO2) is the most investigated crystalline oxide in the surface science of metal oxides. Its physical and chemical properties are dominantly determined by its surface condition. Ti3+surface defect (TSD) is one of the most important surface defects in TiO2. According to publications by other groups and the studies carried out in our laboratory, the formation mechanism of TSD is proposed. The generation, properties, and photocatalytic application of TSD are overviewed; the recent exploration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
122
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 370 publications
(148 citation statements)
references
References 117 publications
8
122
0
4
Order By: Relevance
“…The observation of support reduction is in agreement with the work of Xiong et al, 28 . These authors reported that TiO2 reacted with hydrogen at a temperature below 300 o C. As the temperature increases to above 300 o C, electrons become transferred from the H atoms to O atoms in the lattice of TiO2.…”
Section: Methodssupporting
confidence: 93%
“…The observation of support reduction is in agreement with the work of Xiong et al, 28 . These authors reported that TiO2 reacted with hydrogen at a temperature below 300 o C. As the temperature increases to above 300 o C, electrons become transferred from the H atoms to O atoms in the lattice of TiO2.…”
Section: Methodssupporting
confidence: 93%
“…Hydrogen (H 2 ) was introduced in order to control the oxidation process, thus avoiding the presence of some undesired oxides. This did not result in any significant change in the phase, and it is a common method to improve the surface properties of TiO 2 , creating some defects (oxygen vacancies (OV) and Ti 3+ ), which are important for applications in photocatalysis 30,31 .…”
Section: Methodsmentioning
confidence: 99%
“…25 In the O 1s spectrum, only two peaks at binding energies 529.3 eV, and 530.2 eV are observed which are attributed to lattice oxygen and surface adsorbed OH group. 27 The C 1s spectrum (Fig. 5(c)) includes a strong peak at 284.6 eV and a shoulder at 288.0 eV.…”
Section: Xps Analysismentioning
confidence: 97%